Distinct role of AtCuAOβ- and RBOHD-driven H2O2 production in wound-induced local and systemic leaf-to-leaf and root-to-leaf stomatal closure - Fraudentali, Ilaria; Pedalino, Chiara; D’Incà, Riccardo; Tavladoraki, Paraskevi; Angelini, Riccardo; Cona, Alessandra (Frontiers in Plant Science, 2023)
Polyamines (PAs) are ubiquitous low-molecular-weight aliphatic compounds present in all living organisms and essential for cell growth and differentiation. The developmentally-regulated and stress-induced copper amine oxidases (CuAOs) oxidize PAs to aminoaldehydes producing hydrogen peroxide (H2O2) and ammonia. The Arabidopsis thaliana CuAOβ (AtCuAOβ) was previously reported to be involved in stomatal closure and early root protoxylem differentiation induced by the wound-signal MeJA via apoplastic H2O2 production, suggesting a role of this enzyme in water balance, by modulating xylem-dependent water supply and stomata-dependent water loss under stress conditions. Furthermore, AtCuAOβ has been shown to mediate early differentiation of root protoxylem induced by leaf wounding, which suggests a whole-plant systemic coordination of water supply and loss through stress-induced stomatal responses and root protoxylem phenotypic plasticity. Among apoplastic ROS generators, also D isoform of the respiratory burst oxidase homolog (RBOH) has been shown to be involved in stress-mediated modulation of stomatal closure. In the present study, the specific role of AtCuAOβ and RBOHD in local and systemic perception of leaf and root wounding that triggers stomatal closure was investigated at both injury and distal sites exploiting Atcuaoβ and rbohd insertional mutants. Data evidenced that AtCuAOβ-driven H2O2 production mediates both local and systemic leaf-to-leaf and root-to-leaf responses in relation to stomatal movement, Atcuaoβ mutants being completely unresponsive to leaf or root wounding. Instead, RBOHD-driven ROS production contributes only to systemic leaf-to-leaf and root-to-leaf stomatal closure, rbohd mutants showing a partial unresponsiveness in distal, but not local, responses. Overall, data herein reported allow to hypothesize that RBOHD may act downstream of and cooperate with AtCuAOβ in inducing the oxidative burst that leads to systemic wound-triggered stomatal closure.